Surgical management of benign noninfected urachal cysts in adult patients: two case reports - Asma Sghaier; Eya Lamloum; Mehdi Debaibi; Azza Sridi; Adnene Chouchene (Journal of Medical Case Reports, 2023)
Abstract Background Abnormalities of the urachus include the patent urachus, cysts, sinus, and fistula. Each of these entities represents a failure of complete obliteration of the urachus. Contrary to other urachus anomalies, urachal cysts are usually small and silent unless they are infected. The diagnosis is often made during childhood. A benign noninfected urachal cyst discovered in adulthood is a rare condition. Case presentation Herein we report two cases of benign noninfected urachal cysts in adults. The first case is a 26-year-old Tunisian white man who presented with complaints of clear fluid draining from the base of the umbilicus evolving for a week, with no other associated symptoms. The other case was 27-year-old Tunisian white woman who was referred to the surgery department with a history of intermittent draining of clear fluid from the umbilicus. The two cases had laparoscopic resection of urachus cysts. Discussion Laparoscopy represents a good alternative for the management of persistent or infected urachus, especially when this is suspected, despite a lack of radiological evidence. Laparoscopy in the management of urachal cysts is safe, effective, and offers good cosmesis, with all the advantages of a minimally invasive approach. Conclusion Managing persistent and symptomatic urachal anomalies requires a wide surgical excision. Such intervention is recommended to prevent symptom recurrence and complications, most notably malignant degeneration. A laparoscopic approach offers excellent outcomes, and is recommended to treat these abnormalities.